2014
DOI: 10.4244/eijv9i11a216
|View full text |Cite
|
Sign up to set email alerts
|

Transfemoral aortic valve replacement with the repositionable Lotus Valve System in high surgical risk patients: the REPRISE I study

Abstract: Initial results support proof-of-concept with the Lotus Valve for TAVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
67
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 45 publications
13
67
3
4
Order By: Relevance
“…8 LOTUS implantation is frequently associated with atrioventricular block requiring PPM. 7,8 This is possibly because of greater expansion into the left ventricular outflow tract with compression of the septal conduction pathways, extensive metal burden, and the fact that this valve is longer than the SAPIEN XT valve, leading to deeper settlement.…”
Section: One-year Cumulative Clinical Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…8 LOTUS implantation is frequently associated with atrioventricular block requiring PPM. 7,8 This is possibly because of greater expansion into the left ventricular outflow tract with compression of the septal conduction pathways, extensive metal burden, and the fact that this valve is longer than the SAPIEN XT valve, leading to deeper settlement.…”
Section: One-year Cumulative Clinical Outcomesmentioning
confidence: 99%
“…In addition, the presence of an adaptive seal around the outer aspect of the lower valve frame appears to reduce PVL by occupying residual interstices between the frame and native annulus. 7,8 Gooley et al reported that in comparison of LOTUS versus CoreValve groups, there was significant difference in terms of post-procedural PVL. 17 Furthermore, Wöhrle et al reported that in a comparison of LOTUS and SAPIEN 3 groups, there was no post-procedural moderate or severe PVL.…”
Section: One-year Cumulative Clinical Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…The REPRISE I Trial (Repositionable Percutaneous Replacement of Stenotic Aortic valve Through Implantation of Lotus-Valve System) was a proof-of-concept study with the Lotus valve for TAVR with a procedural success rate of 100% (n = 11) [9]. The REPRISE II study showed that the valve was successfully implanted in all patients, with no cases of valve embolization, ectopic valve deployment, or additional valve implantation.…”
Section: Introductionmentioning
confidence: 99%